Penggunaan Media PowerPoint untuk Meningkatkan Hasil Belajar IPS - Romadhon, Dwi Nanda Akhmad (Jurnal Didaktika Pendidikan Dasar, 2025)
Learning outcomes are one indicator of success in implementing the learning process. The achievement of learning outcomes is influenced by various factors. One of the most important factors is the use of media that is not in accordance with the characteristics of students. Conditions that occurred in the class IX B reached the value of KKM 77 only 20% of 34 students. This study aims to determine the use of Powerpoint learning media in improving the learning outcomes of social studies on World War II material for class IX B students at SMPN 21 Tanjung Jabung Timur. Methods and techniques of research using ARC, with the subject of the study amounted to 34 students SMPN 21 Tanjung Jabung East. The variables studied include learning outcomes and implementation of learning scenarios for 2 cycles. The results of this study indicate that (1) there is an increase in student learning outcomes from the average score of 71.47 with the completeness of classical learning 47% in cycle I to the average value of 82.20 with 88% classical learning completeness in cycle II. It can be concluded that the increase in student learning outcomes was 88% in the "high" category after the use of Powerpoint media. Cycle I has not reached the complete category classically (53%), in Cycle II it has reached the complete category classically (88%) and it has been shown to have a significant increase in the completeness of student learning outcomes from 53% to 88%.